Alternative dimerization interfaces in the glucocorticoid receptor-α ligand binding domain - Bianchetti, Laurent; Wassmer, Bianca; Defosset, Audrey; Smertina, Anna; Tiberti, Marion L.; Stote, Roland H.; Dejaegere, Annick (Biochimica et biophysica acta. General subjects, 2018)
Nuclear hormone receptors (NRs) constitute a large family of multi-domain ligand-activated transcription factors. Dimerization is essential for their regulation, and both DNA binding domain (DBD) and ligand binding domain (LBD) are implicated in dimerization. Intriguingly, the glucocorticoid receptor-α (GRα) presents a DBD dimeric architecture similar to that of the homologous estrogen receptor-α (ERα), but an atypical dimeric architecture for the LBD. The physiological relevance of the proposed GRα LBD dimer is a subject of debate. We analyzed all GRα LBD homodimers observed in crystals using an energetic analysis based on the PISA and on the MM/PBSA methods and a sequence conservation analysis, using the ERα LBD dimer as a reference point. Several dimeric assemblies were observed for GRα LBD. The assembly generally taken to be physiologically relevant showed weak binding free energy and no significant residue conservation at the contact interface, while an alternative homodimer mediated by both helix 9 and C-terminal residues showed significant binding free energy and residue conservation. However, none of the GRα LBD assemblies found in crystals are as stable or conserved as the canonical ERα LBD dimer. GRα C-terminal sequence (F-domain) forms a steric obstacle to the canonical dimer assembly in all available structures. Our analysis calls for a re-examination of the currently accepted GRα homodimer structure and experimental investigations of the alternative architectures. This work questions the validity of the currently accepted architecture. This has implications for interpreting physiological data and for therapeutic design pertaining to glucocorticoid research. •Energetic and sequence conservation analysis of GRα LBD homodimers question the currently accepted dimer architecture.•A more stable and more conserved alternative dimeric assembly than that emphasized in the current literature is proposed.•Comparison with ERα dimer architecture highlights specific features of GRα assembly relevant for signalling.